Learning to teach art and design in the secondary school a companion to school experience - Addison, Nicholas 1954-; Burgess, Lesley 1952- (Learning to teach subjects in the secondary school series, 2015)
"Learning to Teach Art and Design in the Secondary School explores a range of approaches to teaching and learning and provides a conceptual and practical framework for understanding the diverse nature of art and design in the secondary school curriculum.